Slavery's pedagogy: memories excerpted from a judicial process - Capelo, Maria Regina Clivati (Cadernos CERU, 2006)
The study focus on the circumstances lived by a slave accused of homicide. The accusation resulted in a 4-year criminal process during which the slave was incarcerated, despite the fact that there was no substantial evidence of her involvement in the crime. The central hypothesis of this research is related to the network of social interdependency resulting in subaltern subjectivity, a type of slavery pedagogy that resulted in domestication. Aside from the enormous economical differences between slaveholders and slaves, whites and blacks, the ethnical differences were used as classification strategy among the slaves themselves. The vast distance existing between the past and present did not completely fade slavery marks in our society. In that context, Ambrozina was the weakest link of them all, for besides being black and a slave, she was a girl.